Function integration concept design applied on CFRP cross leaf spring suspension. (2017) - Airale, Andrea; Ferraris, Alessandro; Xu, Shuang; Sisca, Lorenzo; Massai, Paolo
In automotive systems, lightweight design is nowadays a mandatory target. Suspension systems, which are a safety system and contribute to overall vehicle performance (dynamic, comfort, noise and vibration, etc…), are one of the most complex systems in which to achieve lightweight targets. This paper discusses the development of a CFRP Cross Leaf Spring Prototype (TRL 6). The entire workflow, starting from kinematic design, multibody vehicle dynamics analysis, finite element method (FEM) structural analysis, prototype construction, testing and correlations is shown. Also studied in this project is the integration and applications of advanced continuous fibre reinforced thermoplastic polymer (CFRTP). This system, in comparison to traditional solutions, could guarantee: around 75% weight savings, suspension component optimisation, an optimisation of the suspension volume (resulting in more space for vehicle occupants), easy integration of advanced process using CFRTP, and a sustainable cost solution.